Structural Strengthening Behavior of Beams using Steel Plates (International Journal of Scientific Research and Management (IJSRM), 2017)
This study presents the investigation of structural response of strengthened cantilever beams using steel plates. For the purpose a rectangular section is selected and full-scaled beams are three dimensionally modeled using finite element method. The dimensions of the beams such as width, height and length are selected as 25 cm, 50 cm and 300 cm, respectively. In the study, three different beam models are included to investigate the structural response of beams. First model is called as Model-1 and it considers only a traditional RC beam. Second model is called as Model-2 and it considers rectangular concrete section covered with steel plates. In model-2, thickness of the steel plate is selected as 2.5 mm. Third model is called as Model-3 and it is similar to Model-2, but the thickness of the steel plate is selected as 5 mm. Model-2 and Model-3 are used to strength the Model-1 to investigate the strengthening effects on the structural response of the traditional beam. In the study, all models and analyses are performed using ANSYS software. The rebar, concrete and steel plates are represented with LINK180, SOLID65, and SOLID185 elements, respectively. Boundary conditions are defined on started section as fixed and ended section as free. Interface between concrete and steel plates is assumed as bounded. Nonlinear pushover analyses of beam models are performed and displacements and stresses obtained from analyses are presented as graphics through beam length and contour diagrams. The results showed that strengthened beams (Model-2 and Model-3) have more capacity compared to traditional beam (Model-1).